2013
DOI: 10.4102/sajems.v16i3.404
|View full text |Cite
|
Sign up to set email alerts
|

Product innovation of private health insurers in South Africa and the impact of entrepreneurial orientation

Abstract: Recognising that health insurer product innovation plays a critical role in aligning incentives among all stakeholders in the healthcare value chain, this study investigates the relationship between the level of health insurer product innovation and entrepreneurial orientation (EO). Taking cognisance of the importance of external collaboration between health insurers and healthcare service providers, the study is able to diagnose perceptions of strategic regulatory factors and their impact on levels of EO. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…One stream of literature considers management practices particularly prevalent in Africa; for example, some firms in South Africa take advantage of the benefits of barter trading, minimizing potential hazards through dedicated personnel responsible for ensuring accountability and good practice (Oliver & Mpinganjira, 2011). Another stream focuses on more widely studied practices targeted at building entrepreneurial capacity and innovation within management teams (Urban & Streak, 2013;Van Wyk & Adonisi, 2011) and new product development models adopted by managers (Yan & Makinde, 2011).…”
Section: Managerial Capacitymentioning
confidence: 99%
“…One stream of literature considers management practices particularly prevalent in Africa; for example, some firms in South Africa take advantage of the benefits of barter trading, minimizing potential hazards through dedicated personnel responsible for ensuring accountability and good practice (Oliver & Mpinganjira, 2011). Another stream focuses on more widely studied practices targeted at building entrepreneurial capacity and innovation within management teams (Urban & Streak, 2013;Van Wyk & Adonisi, 2011) and new product development models adopted by managers (Yan & Makinde, 2011).…”
Section: Managerial Capacitymentioning
confidence: 99%
“…In their extensive review of 154 research articles on African business management, George et al (2016) found three overarching challenges for entrepreneurship in Africa which apply also to challenges in ASM. The first is navigating institutional voids and the need to work around weak institutional infrastructure to find value-creation opportunities (Ngobo & Fouda, 2012;Ofori-Dankwa & Julian, 2013), the second is building capability in managers (Mano, Iddrisu, Yoshino, & Sonobe, 2012) and employees (Urban & Streak, 2013) and the third is enabling opportunity by implementing new market entry strategies. All these challenges are pertinent to my research.…”
Section: Chapter Overviewmentioning
confidence: 99%